2010
DOI: 10.1111/j.1556-4029.2010.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Typing for the Identification of Old Skeletal Remains from Korean War Victims*

Abstract: The identification of missing casualties of the Korean War (1950-1953) has been performed using mitochondrial DNA (mtDNA) profiles, but recent advances in DNA extraction techniques and approaches using smaller amplicons have significantly increased the possibility of obtaining DNA profiles from highly degraded skeletal remains. Therefore, 21 skeletal remains of Korean War victims and 24 samples from biological relatives of the supposed victims were selected based on circumstantial evidence and/or mtDNA-matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In addition, the multiplex system presented here requires only two or three amplification reactions per sample to amplify mtDNA HV regions, whereas a previous method based on monoplex amplification required five and eight amplification reactions per sample using midi‐primer set and mini‐primer set, respectively . Moreover, the success rate of the multiplex system (>95%) was high enough to compensate the need for additional amplification of the failed PCR fragment.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the multiplex system presented here requires only two or three amplification reactions per sample to amplify mtDNA HV regions, whereas a previous method based on monoplex amplification required five and eight amplification reactions per sample using midi‐primer set and mini‐primer set, respectively . Moreover, the success rate of the multiplex system (>95%) was high enough to compensate the need for additional amplification of the failed PCR fragment.…”
Section: Resultsmentioning
confidence: 97%
“…Some Y‐STR loci (DYS390, DYS391, DYS392, DYS438, DYS439, and DYS635) of the AmpF l STR Yfiler kit analysis were replaced with custom‐designed primer sets for the same loci. Briefly, the designs of four primers (DYS390, DYS392, DYS438, and DYS653) were based upon those already reported in the work of Lee et al . On the other hand, DYS391 and DYS439 were newly designed by us using FastPCR program (Primer Digital Ltd., Helsinki, Finland) (Data S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, Sturk et al showed that under modified Yfiler system amplification parameters, Y‐STR profiles from highly degraded skeletal samples could be obtained. Enhancement to Yfiler kit analysis also was achieved by the coupled use of new primer sets designed to move as close as possible to the target Y‐STR locus area . By replacing some Y‐STR profiles of the Yfiler kit with those of newly designed primer sets for the same loci (DYS390, DYS391, DYS635, DYS438, DYS439, DYS392, DYS385), genetic information that was not be obtained by the sole use of the Yfiler system could be recovered successfully from the degraded DNA samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many scenarios encountered in forensic casework in which bone may be the only viable sample type for DNA testing, including fires, terrorist attacks, natural disasters, war conflicts, airline crashes, homicide, and mass graves from oppressive regimes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In addition, skeletal remains often are the only samples available in historical and archaeological cases [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%